The Role of Canva-Based Learning Media in Improving Mathematical Critical Thinking Skills in Elementary School Students’ Data Analysis Material - Nur Afiah; Ety Mukhlesi Yeni; Aminah Aminah (Journal of Educational Sciences, 2026)
The development of digital technology provides opportunities for teachers to create more interactive and engaging learning experiences. This study aims to determine the effectiveness of Canva-based interactive learning media in improving fifth-grade  students’ Mathematical Critical Thinking skills in data analysis material. This research employed a quantitative approach using a quasi-experimental method with a non-equivalent comparison-group design involving a control class and an experimental class. Data were collected through pretest and posttest instruments. The results showed that the experimental class experienced a significant increase in the average score, from 47.86 in the pretest to 70.00 in the posttest, indicating a substantial improvement compared to the control class. The data were analyzed using normality, homogeneity, and independent samples t-tests. The normality test results indicated that all data were normally distributed (Sig. > 0.05), while the homogeneity test showed equal variances between groups (Sig. = 0.733 > 0.05). Furthermore, the t-test result showed a significance value of 0.000 (< 0.05), indicating a significant difference between the two groups. These findings demonstrate that Canva-based interactive learning media is effective in enhancing  students’ Mathematical Critical Thinking skills in elementary school data analysis learning.